The Untranslatability of Dreams - Chandran, University of Hyderabad, India, K. Narayana (Asiatic: IIUM Journal of English Language and Literature, 2011)
This short meditation on dreamwork-narrative wonders why dreams are not easily translated. It takes off from Derridaâ€™s remark in Writing and Difference that â€œsince the materiality of the signifier constitutes the idiom of every dream scene, dreams are untranslatableâ€ (210). Working through a secular, a Hindu and a Buddhist parable respectively, this essay considers 5 possible explanations for the untranslatability of dreams. It proposes that there might be no material to translate, as in the fiction whose â€œmaterialityâ€ we assume and which we are used to reading and interpreting in broad daylight. Dreams however continue to be immaterial while the translator works away at his desk. We havenâ€™t yet known it as either material â€œworkâ€ or â€œtext,â€ so there might yet be no need to trouble ourselves with the death of its author.